PERENCANAAN DAN KONFLIK : Pada Pengembangan Wilayah Berbasis Sumber Daya Alam di Hulu Sungai Bengawan Solo - Hudya Syarif Umrony; Mohammad Muktiali (Diponegoro University, 2017)
Upstream of the Solo River in Wonogiri has a rich variety of natural resources. But in their usage, conflicts occur both intra-sector and between sectors. This article examines the conflicts in the utilization of natural resources in the upper reaches of the Solo River in Wonogiri and model / approach to planning for the sectors that experienced the conflict.In sectors utilization of natural resources that conflict, most of the planning takes a